2019
DOI: 10.1177/1203475418818073
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Platelet-Rich Plasma in the Field of Hair Restoration and Facial Aesthetics—A Systematic Review and Meta-analysis

Abstract: As a promising alternative to traditional treatment, platelet-rich plasma (PRP) is being used to encourage hair growth through the release of growth factors and cytokines. In addition to hair restoration, PRP’s multifactorial capabilities can also be used to treat aging skin, facial scarring, and acne. The purpose of this review is to critically examine the success of PRP in the field of dermatology, with specific attention to the role of PRP in hair restoration. Where possible, meta-analyses were used to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 145 publications
(288 reference statements)
2
42
0
2
Order By: Relevance
“…It has been used successfully in several aesthetic fields and skin rejuvenation. 6 PPP gel is another plasma formulation that is rich in fibrin and gelled proteins which provide volume and stability at the site of injection. It is recently suggested for soft tissue augmentation as it is a semi-solid, easily injectable material that generally fulfills the standard safety requirements.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used successfully in several aesthetic fields and skin rejuvenation. 6 PPP gel is another plasma formulation that is rich in fibrin and gelled proteins which provide volume and stability at the site of injection. It is recently suggested for soft tissue augmentation as it is a semi-solid, easily injectable material that generally fulfills the standard safety requirements.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis including 23 studies of PRP use in AGA (7 randomized controlled trials, with 6 studies having a half-head design) reported that monthly PRP administration for 3 months produced significant improvement in total hair density, compared to placebo, with most studies using a half-head design. [ 17 ] The authors further reported that while 26% of studies showed strong evidence for the use of PRP in AGA, 30% of studies showed moderate-level evidence and as high as 47% of studies had low evidence. Whereas another systematic review concluded the lack of enough evidence for the use of PRP-based therapies in androgenetic alopecia.…”
Section: Prp In Dermatologymentioning
confidence: 99%
“…Platelet-rich plasma (PRP) is an autologous product that is prepared by centrifuging from patients' own venous blood (Giordano, Romeo, & Lankinen, 2017). Recently, PRP has emerged as a promising agent for treating alopecias and a number of reports have been published showing encouraging results, particularly for androgenetic alopecia and alopecia areata (Giordano et al, 2017;Gupta et al, 2019;Trink et al, 2013); however, its efficacy in FFA is unknown. infiltration were observed on the vertical sections.…”
mentioning
confidence: 99%
“…There are only a few case reports, which assess the use of PRP in primary cicatricial alopecia (Bolan ca, Goren, Getaldi c-Švarc, Vu ci c, & Šitum, 2018; Dina & Aguh, 2018;Gupta et al, 2019;Jha, 2019). It has been used to treat lichen planopilaris and central centrifugal cicatricial alopecia, wherein global improvement of hair density and regression of the symptoms and signs was achieved in the patients (Dina & Aguh, 2018;Bolan ca et al, 2018;Jha, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation